Referência anatômica de acesso à base do crânio na transição crânio cervical centrada no processo transverso de C1, sistematizando o uso de quadrantes - Silvio Pereira Ramos Junior (2017)
Background: posterior fossa tumors and those in the craniocervical transition are highly challenging due to their deep location, the number of noble structures involved and the anatomical distortion they cause. The literature describes several surgical approaches for these regions. However, there is a gap concerning the anatomical study of the medial portion of the craniocervical transition. Objective: To perform an anatomical study regarding skull base access in the craniocervical transition centered on the C1 transverse process, systematizing the use of quadrants. Methods: We describe the anatomical relationships in 10 cadavers, using the C1 transverse process as a point of reference and the outline in quadrants. Results: Using the C1 transverse process as a reference and the outline of quadrants, enabled the visualization of the anatomical structures involved in each quadrant in an organized fashion, from the skin surface all the way to deep nerve and vascular structures. We hereby, used a surgical case to exemplify the applicability of the C1 transverse process-based access and the use of the quadrants during surgery to treat a jugulotympanic tumor. The relevance of this system used in other pathologies involving all quadrants, such as in the Eagle's syndrome, jugular foramen meningiomas and the chordomas that destroy the condyles, the lower lateral clivus, and the top portion of the cervical spine, was evidenced. Conclusion: The systematization of the anatomical study by means of quadrants, from the C1 process, allows precise identification of the structures involved in the accesses to the base of the skull in the cervical skull transition, and adequate planning of the surgical approach.